Pengaruh Metode Eksperimen Terhadap Hasil Belajar Peserta didik Pada Materi Sumber Energi Di Kelas IV Negeri 1 Mata Ie Aceh Besar - Riska Yani; Alfiati Syafrina; Intan Safiah (Universitas Syiah Kuala, 2023)
Experiment is a teaching method in which students experiment with something and provide opportunities for individuals or small groups of students to practice the process or experiment. The question posed in this study is whether the experimental method has a significant effect on the energy learning outcomes of students at SD Negeri 1 Mata Ie Aceh Besar level IV. This study aims to describe the significant effect of the experimental method on energy learning outcomes for students of SD Negeri 1 Mata Ie Aceh Besar grade IV. This research method is quantitative, which is a type of quasi-experimental research with a pretest-posttest design. The subjects of this study were 14 men and 10 women. Use test data collection techniques, namely pre-test and post-test. Data Analysis Techniques The t-test was used at a significance level of α = 0.05. Data analysis, according to the results of tcount ttable = 6.20 ˃ 1.711. Then it was found that Ho was rejected and H1 was accepted. Therefore, the conclusion of this study is that the experimental approach has a significant effect on student learning outcomes on energy material at SD Negeri 1 Mata Ie Aceh Besar class IV can improve student learning outcomes and be accepted.